Mary Shelley’s Frankenstein, the Guillotine, and Modern Ontological Anxiety - Lacefield, Kristen (Text Matters: A Journal of Literature, Theory and Culture, 2016)
This essay begins by examining the rhetorical significance of the guillotine, an important symbol during the Romantic Period. Lacefield argues that the guillotine symbolized a range of modern ontological juxtapositions and antinomies during the period. Moreover, she argues that the guillotine influenced Mary Shelley’s novel Frankenstein through Giovanni Aldini, a scientist who experimented on guillotined corpses during the French Revolution and inspired Shelley’s characterization of Victor Frankenstein. Given the importance of the guillotine as a powerful metaphor for anxieties emergent during this period, Lacefield employs it as a clue signaling a labyrinth of modern meanings embedded in Shelley’s novel, as well as the films they anticipated. In particular, Lacefield analyzes the significance of the guillotine slice itself—the uneasy, indeterminate line that simultaneously separates and joins categories such as life/death, mind/body, spirit/matter, and nature/technology. Lacefield’s interdisciplinary analysis analyzes motifs of decapitation/dismemberment in Frankenstein and then moves into a discussion of the novel’s exploration of the ontological categories specified above. For example, Frankenstein’s Creature, as a kind of cyborg, exists on the contested theoretical “slice” within a number of antinomies: nature/tech, human/inhuman (alive/dead), matter/spirit, etc. These are interesting juxtapositions that point to tensions within each set of categories, and Lacefield discusses the relevance of such dichotomies for questions of modernity posed by materialist theory and technological innovation. Additionally, she incorporates a discussion of films that fuse Shelley’s themes with appeals to twentieth-century and post-millennium audiences.